Effect of Watering Frequency on The Growth and Yield of Oyster Mushrooms (Pleurotus ostreatus) - Agus Saputera; Antar Sofyan; Riza Adrianoor Saputra; Noorkomala Sari (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2020)
Oyster mushrooms have the conditions of growing at low temperatures and high relative humidity, so when you want to cultivate it is needed an appropriate environment for the growth and development of oyster mushroom. Banjarbaru City tends to have high temperatures with a relative humidity that tends to below. This is quite different from the requirements for growing oyster mushrooms which require low temperatures with relatively high humidity. One of the easiest and cheapest methods to maintain temperature and relative humidity to remain ideal and appropriate is to water the surrounding oyster mushrooms growing media, so knowledge of the most appropriate and ideal watering frequency for growth and development of oyster mushrooms is needed. The environmental design used was a Completely Randomized Design (CRD), a single factor with 4 treatments, 5 replications, so that 20 experimental units were obtained. The treatments are p1 = once watering per day, p2 = twice watering per day, p3 = three times watering per day, p4 = four times watering per day. The result showed that the watering frequency showed significant difference to the growth time of oyster mushroom shoots and the wet weight of oyster mushrooms. The best treatment in accelerating the growth time of oyster mushroom shoots and increasing the wet weight of oyster mushrooms is four times watering frequency per day.